2005
DOI: 10.1136/jmg.2004.030106
|View full text |Cite
|
Sign up to set email alerts
|

Functional polymorphisms in cell death pathway genes FAS and FASL contribute to risk of lung cancer

Abstract: Background: The FAS and FASL system plays a key role in regulating apoptotic cell death and corruption of this signalling pathway has been shown to participate in immune escape and tumorigenesis. There is reduced expression of FAS but elevated expression of FASL in many types of human cancers including lung cancer. We recently reported an association between functional polymorphisms in FAS (21377GRA) and FASL (2844TRC) and risk of oesophageal cancer. Objective: To examine the contribution of these polymorphism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

14
109
1
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(125 citation statements)
references
References 32 publications
14
109
1
1
Order By: Relevance
“…Hypothetically the FasL polymorphism is important for progression to invasive cervical cancer but not for susceptibility to long-term HPV infection and cervical lesions. This is supported by reported associations of the FasL 2844 C-allele with other cancer sites, such as the esophagus, 52 lung 53 and bladder. 54 The C-allele increases expression of FasL 27 and many studies report increased expression of FasL by malignant cells in destruction of local tissue, invasion and metastasis.…”
Section: Discussionsupporting
confidence: 69%
“…Hypothetically the FasL polymorphism is important for progression to invasive cervical cancer but not for susceptibility to long-term HPV infection and cervical lesions. This is supported by reported associations of the FasL 2844 C-allele with other cancer sites, such as the esophagus, 52 lung 53 and bladder. 54 The C-allele increases expression of FasL 27 and many studies report increased expression of FasL by malignant cells in destruction of local tissue, invasion and metastasis.…”
Section: Discussionsupporting
confidence: 69%
“…7,8 In addition, polymorphisms in the FAS gene and perhaps also in the FASL gene that impair apoptotic signal transduction are associated with a high risk of cancer in various models. [9][10][11][12][13][14][15][16][17][18][19][20][21][22] Thus, the FAS/FASL system appears to have a role in the development and progression of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…A series of epidemiologic studies conducted by Lin's group indicated that subjects with the FasL À844CC genotype have a higher cancer risk than those with the FasL À844TTþTC genotype, including increased risk of esophageal, cervical, lung, breast, and pancreatic carcinomas (18)(19)(20)(21)(22). However, the FasL À844T/C genotype was not associated with lung cancer risk in our case-control study (385 cases and 308 controls), which might be explained by differences in the studied case populations (FasL À844CC genotype: 61.2% for Chinese vs. 46.4% for Taiwanese).…”
Section: Discussionmentioning
confidence: 99%
“…A series of case-controlled studies from Lin's group indicated that the functional FasL À844T/C polymorphism in a Chinese population was associated with an increased risk of different human cancers, including those of the cervix, lung, esophagus, breast, and pancreas (18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%